The effect of HIV self-testing delivery models on female sex workers’ sexual behaviors: a randomized controlled trial in urban Uganda - Ortblad, Katrina; Bärnighausen, Till (Aids and behavior, 2019)
HIV self-testing increases recent and frequent HIV testing among female sex workers (FSWs) in urban Uganda. Using results from a randomized controlled trial, we aim to establish the effect of HIV self-testing delivery models on FSWs’ sexual behaviors in this setting. Clusters of one peer educator and eight participants were 1:1:1 randomized to: (1) direct provision of an HIV self-test, (2) provision of a coupon for facility collection of an HIV self-test, or (3) referral to standard-of-care HIV testing services. Sexual behaviors were self-reported at 1 and 4 months. From October to November 2016, 960 participants were enrolled and randomized. At 4 months, there were no statistically significant differences in participants’ sexual behaviors, including inconsistent condom use, across study arms. We do not find any changes in sexual risk-taking among FSWs in response to the delivery of HIV self-tests. Routine policies for HIV self-testing are likely a behaviorally safe component of comprehensive HIV prevention strategies.